2003
DOI: 10.1038/oby.2003.188
|View full text |Cite
|
Sign up to set email alerts
|

Sibutramine Treatment in Obesity: Predictors of Weight Loss Including Rorschach Personality Data

Abstract: . The treatment comprised 15 mg of sibutramine administered daily and monthly dietary advice. Weight loss after 6 months of treatment was evaluated. For psychological assessment, the Rorschach method (Comprehensive System) and the Beck Depression Inventory were used. Results: A multiple linear regression model including the Rorschach predictors' physical demand states (animal movement, designated as FM) being intrusive or difficult to hold and a dependency orientation (food contents) could explain 47% of 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
2
18
0
1
Order By: Relevance
“…In the same study,27 self-inspect ability (which means an ability to monitor and reflect on one’s behavior and thinking) was related to weight loss but was not a predictor.…”
Section: Predictors Associated With Sibutramine Treatmentsmentioning
confidence: 91%
See 1 more Smart Citation
“…In the same study,27 self-inspect ability (which means an ability to monitor and reflect on one’s behavior and thinking) was related to weight loss but was not a predictor.…”
Section: Predictors Associated With Sibutramine Treatmentsmentioning
confidence: 91%
“…A study in 200327 demonstrated that patients with more deviating levels (elevated or lowered from the mean) of physical demand states (inborn and natural primary drives, including hunger) and dependency orientation (which implies preoccupation with oral activity such as eating and dependency on food, and which is typical of people vulnerable to social isolation) lost more weight when treated with sibutramine ( r = 0.533, P = 0.002 and r = 0.478, P = 0.008, respectively). Initial signs of difficulties concerning physical demand states were strong positive predictors of weight loss ( r = 0.533, P = 0.002), explaining 27% alone.…”
Section: Predictors Associated With Sibutramine Treatmentsmentioning
confidence: 99%
“…It is possible, therefore, that the profiling of personality traits could be matched with the various weight loss programs to identify those that could result in improved weight loss outcomes for the individuals concerned. Indeed, a number of studies have investigated the link between personality traits and weight loss with varying degrees of success [13-16]. However, their use of different tests to measure different traits makes it difficult to compare the findings.…”
Section: Introductionmentioning
confidence: 99%
“…The pretreatment body weight seems to be an independent predictor of the extent of weight loss and its maintenance by sibutramine [45,46] . Bray et al [47] found that weight lost with sibutramine at the fourth week of treatment was the predictive of persistent weight loss in 24 weeks.…”
Section: Clinical Effi Cacy Of Sibutramine In Weight Loss and Maintenmentioning
confidence: 92%